"Géoscola" or the short story of the implementation of a territorial geoportal as an assistance to public school management - Michelet, Jacques; Périsset, Danièle (Swiss Journal of Educational Research, 2022)
The Géoscola platform grew out of the need to have an effective tool for steering and helping decision-making in the public school system in the Canton of Valais. Its creation results of an approach between educational sciences and geography. Information on the structure of the school system is based on the nomenclature of educational subdivisions with a territorial perspective. This was achieved with the adaptation of "Géoclip Air", a geoportal designed and used primarily by statistical institutes. This article reports on the technical and human adventure this project represented. It also analyses the process thus initiated, in collaboration with various institutional actors, which makes it essential to consider sensitive administrative, political and ethical implications and requirements.